Effectiveness of Tailored Care Intervention Program on Biochemical Outcomes of Patients With Diabetes in Indonesia: A Randomized Controlled Trial - Satriya Pranata; Shu-Fang Vivienne Wu; Tsae-Jyy Tiffany Wang; Shu-Yuan Liang; Yeu-Hui Chuang; Kuo-Cheng Lu; Difran Nobel Bistara (Journal of Client-centered Nursing Care, 2023)
Background: Although patients with diabetes have common problems, their educational needs may differ, and they have the right to participate in planning and implementing individual or group healthcare programs. Because there are no proper care interventions for diabetic patients in Indonesia, this study evaluated the efficacy of a tailored care intervention program on some blood biochemical outcomes among Indonesian patients with diabetes. Methods: We conducted a randomized controlled trial (RCT) with a pre-test-post-test design. We recruited 163 diabetic patients referred to Moyo Hilir and Moyo Hulu primary healthcare facilities in Sumbawa City, Indonesia, from January to April 2021. The subjects were randomly assigned to either intervention (n=80) or control (n=83) groups. The intervention group received a tailored care intervention program with 7 elements implemented through four stages: 1) brief deductive teaching, 2) self-management assessment, 3) brainstorming and support group, and 4) Follow-up. The control group received routine education. The study data were collected at baseline and three months after the intervention. The outcome measures were blood glucose levels, cholesterol, triglyceride, and triglyceride glucose index. IBM SPSS software, version 20 was used for statistical analysis. The obtained data were analyzed by descriptive (frequency distributions, percentages, Mean±SD) and inferential statistics (Chi-square, independent t-test, and paired t-test). The significance level was set at P<0.05. Results: According to the independent t-test, there were no significant differences in blood glucose levels of the groups before and after the intervention. There were also no significant differences in the groups’ cholesterol, triglyceride, and triglyceride glucose index before the intervention, but significant differences were seen after the intervention (P=0.000). However, the significance moved in a negative direction. According to paired t-test, blood glucose level, triglyceride, and triglyceride glucose index increased in the control group but decreased in the intervention group, although it was not significant. On the other hand, cholesterol levels increased in both intervention and control groups, which was not significant. Conclusion: Although no significant findings were obtained, the glucose level, triglyceride, and glucose triglyceride index values of the intervention group were better than the control group, but not in terms of cholesterol level. Tailored care intervention programs can improve biochemical indicators, especially for blood glucose levels, triglycerides, and triglyceride glucose index; however, it seems that a follow-up study beyond three months is needed to be performed in the future.